2016
DOI: 10.1055/s-0036-1581075
|View full text |Cite
|
Sign up to set email alerts
|

Free Vascularized Fibular Graft is Reliable in Upper Extremity Long-Bone Reconstruction with Good Long-Term Outcomes

Abstract: Background Free vascularized fibular graft is useful in upper extremity long-bone reconstruction. The authors studied the reliability and long-term outcomes of this technique. Methods The authors included 20 patients with a minimum follow-up of 24 months in this study, and retrospectively reviewed patients' hospital records and used a preinformation form, the Disabilities of the Arm, Shoulder and Hand (DASH), the Lower Extremity Functional Scale (LEFS), and the 15D health-related quality of life (HRQoL) instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…[ 3 ] This technique has been proved effective in many previous studies. [ 4 , 5 ] However, the side effect of this method in small patients is still questioned for many years. Abdul et al report 8 cases of fibular graft section in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] This technique has been proved effective in many previous studies. [ 4 , 5 ] However, the side effect of this method in small patients is still questioned for many years. Abdul et al report 8 cases of fibular graft section in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…There has been several papers on the use of the vascularized free fibula in the treatment of upper extremity long bone defects most of these have been limited case series addressing a mixed bag of upper extremity defects including tumor resection, aseptic non-union and infected non-union of bone [14][15][16][17][18][19][20][21][22][23][24][25]. None have addressed solely the treatment of infected non-union of bone with particular reference to the surgical technique and outcome in detail.…”
Section: Although Amputation Remains An Option Poor Results Of Upper Extremitymentioning
confidence: 99%
“…In their study, Kessler et al (19) reported that the average ICGB amount obtained from subjects with a mean age of 44 years was 9 cm 3 (range, 5-12 cm 3 ) from the anterior and 25.5 cm 3 (range, 17-29 cm 3 ) from the posterior. Although the amount of graft taken is higher than the posterior, it is possible to come across reports of more blood loss (1).…”
Section: Discussionmentioning
confidence: 97%
“…Conventional cancellous bone grafts have commonly served to reconstruct bone defects smaller than 6 cm. However, larger defects and cases of impaired vasculature require biomaterials, endoprostheses, and vascularized bone transfer (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%